Monte Carlo simulations for medical physics: From fundamental physics to cancer treatment. (January 2017) - Guatelli, S.; Incerti, S.
Highlights: Focus Issue (FI) dedicated to the Monte Carlo (MC) Workshop for Medical Physics. The Monte Carlo workshop took place in April 2016. The event was organised by the Centre For Medical Radiation Physics, Wollongong. The FI contains 12 original, peer reviewed scientific contributions. The papers concern the projects presented in some oral presentations of the event. The contributions include research performed in Europe, US, Asia and Australia.